The Implementation of Narrative Counseling to Improve Students’ Self-Concept - Haslinah Haslinah; Abdullah Pandang (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2020)
This study aims to describe (1) the negative self-concept of the students in Madrasah Aliyah DDI Kanang in Polewali Mandar Regency; (2) the implementation of narrative counseling to improve the self-concept of the students in Madrasah Aliyah DDI Kanang in Polewali Mandar Regency; and (3) the impacts of the implementation of narrative counseling to improve the self-concept of the students in Madrasah Aliyah DDI Kanang in Polewali Mandar Regency. This study used the quasi-experimental design with the quantitative approach. The sample of the study was 20 students in the 11th grade of Madrasah Aliyah DDI Kanang in Polewali Mandar Regency. Data were collected through questionnaires, observations, and interviews and analyzed using the Independent Sample t-Test. The study found that the self-concept of most students in Madrasah Aliyah DDI Kanang in Polewali Mandar Regency was at the moderate level and there was quite a significant difference in the scores of the students’ self-concept before and after the application of narrative counseling. These results suggest that narrative counseling is effective in improving the self-concept of the students in Madrasah Aliyah DDI Kanang in Polewali Mandar Regency.